Coal-fired utility boiler modelling for advanced economical low-NOx combustion controller design. (January 2017) - Zhao, Huirong; Shen, Jiong; Li, Yiguo; Bentsman, Joseph
Abstract: This paper focuses on developing a control-oriented coal-fired utility boiler model for advanced economical Low-NO x combustion (ELNC) controller design. Two boiler combustion models are proposed in this paper: one is a mathematical model describing the key dynamics of the real-time boiler thermal efficiency and the furnace one-dimensional NO x concentration distribution under conventional fuel and overfire air operations; the other recast from the first model is a control-oriented grey-box model with a data-driven furnace combustion submodel. Simulation studies on static and dynamic properties of the first mathematical model indicate that the model can function as a real-time simulator for both advanced boiler combustion control laws testing and generating training and validation data for the control-oriented grey-box model. At the end of this paper, the control-oriented grey-box modelling procedure as well as an optional discrete time linear state-space model are summarised to facilitate model-based advanced combustion controllers design.